Are we talking the same paradigm? Considering methodological choices in health education systematic review. (2nd July 2016) - Gordon, Morris
Abstract: For the past two decades, there have been calls for medical education to become more evidence-based. Whilst previous works have described how to use such methods, there are no works discussing when or why to select different methods from either a conceptual or pragmatic perspective. This question is not to suggest the superiority of such methods, but that having a clear rationale to underpin such choices is key and should be communicated to the reader of such works. Our goal within this manuscript is to consider the philosophical alignment of these different review and synthesis modalities and how this impacts on their suitability to answer different systematic review questions within health education. The key characteristic of a systematic review that should impact the synthesis choice is discussed in detail. By clearly defining this and the related outcome expected from the review and for educators who will receive this outcome, the alignment will become apparent. This will then allow deployment of an appropriate methodology that is fit for purpose and will indeed justify the significant work needed to complete a systematic. Key items discussed are the positivist synthesis methods meta-analysis and content analysis to address questions in the form of 'whether and what' education is effective. These can be juxtaposed with the constructivist aligned thematic analysis and meta-ethnography to address questions in the form of 'why'. The concept of the realist review is also considered. It is proposed that authors of such work should describe their research alignment and the link between question, alignment and evidence synthesis method selected. The process of exploring the range of modalities and their alignment highlights gaps in the researcher's arsenal. Future works are needed to explore the impact of such changes in writing from authors of medical education systematic review.